Compassion fatigue and resilience in palliative care nursing practice: systematic review - Jadhav, Huchcheshwar R.; Pritika; E. T., Dileep; Umar, Mohammed; Pratap, Akhand; Pillai, Akshatha K. Raju; Tongpangkokla Ozukum, S.; Suhashini; Rathore, Khushal Singh; Kawar, Ajay Jyotiram (International Journal of Research in Medical Sciences, 2025)
Palliative care nursing demands continuous compassionate engagement with patients and families experiencing end-of-life challenges. While this empathetic involvement enhances care quality, it also exposes nurses to significant emotional strain, often leading to compassion fatigue (CF) a state of emotional exhaustion, reduced empathy, and depersonalization. Conversely, resilience, defined as the psychological capacity to adapt positively in the face of adversity, serves as a protective factor mitigating CF’s adverse effects. This comprehensive review aimed to synthesize existing evidence on the prevalence, predictors, consequences, and mitigating strategies of CF, alongside the role of resilience among palliative care nurses. A systematic narrative review was conducted using databases including PubMed, CINAHL, Scopus, PsycINFO, and Web of Science (2010-2025), identifying 47 studies that met inclusion criteria. Findings revealed that 30-65% of palliative nurses experience moderate-to-high levels of CF, with contributing factors including emotional exposure, workload, moral distress, and inadequate support. Resilience consistently demonstrated a negative correlation with CF, buffering stress and promoting compassion satisfaction. Interventions such as mindfulness-based stress reduction (MBSR), reflective practice, peer support, and resilience training programs significantly improved coping outcomes. The review highlights resilience as a dynamic and trainable attribute essential for sustaining emotional well-being, professional satisfaction, and high-quality patient care. Institutional strategies emphasizing psychological support, education, and team cohesion are crucial for promoting resilient nursing practice in palliative settings.